Microbial Flora of Corneal Ulcer and their Drugs Sensitivity - Kunwar, Meena; Adhikari, Rishi Kant; Karki, Deep Bahadur (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Corneal ulcer is a leading cause of ocular morbidity and blindness worldwide. Knowledge of the common organism causing corneal ulcers and the sensitivity of the bacteria will help formulate the fi rst line of treatment which would have relatively high percentage of success even in areas devoid of diagnostic facilities. The main objective of this study was to fi nd out commonest organisms that cause corneal ulcers and to determine their antimicrobial susceptibility. Methods: This was a prospective study of 55 consecutive cases of corneal ulcers. Patients who had congenital abnormality of cornea, uncooperative patient not allowing to do corneal scrapping, patient with suspected or confi rmed viral keratitis, Patient with corneal ulcer with HIV positive and all non-infective corneal ulcers were excluded from the study. Results: Of 55 cases enrolled in this study microorganisms were grown from 31 (56%) cases. Of 31 growth positive cases, 17 (54.8%) showed pure bacterial growth, 13 (41.9%) cases showed pure fungal growth and in only 1 (3.2%) case there was mixed (bacteria and fungus) growth. Among the tested antibiotic, sensitivity of Ciprofl oxacin and Gentamicinewas 100% and that of Ceftriaxone was nearly 94%. Almost 20% bacteria were resistant to Chloramphenicol. Sensitivity of newer quinolone (Ofl oxacine) was also not very high, having more than 20% bacteria resistant to it. Conclusions: The commonest organism responsible for bacterial keratitis was strepto. Pneumonia. Ciprofl oxacin and Gentamicin were the most sensitive antibiotics.  Medical Journal of Shree Birendra Hospital; January-June 2013/vol.12/Issue1/14-17DOI: http://dx.doi.org/10.3126/mjsbh.v12i1.9086